2015
DOI: 10.1017/s0022215115002996
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, beliefs and practices related to chronic suppurative otitis media and hearing impairment in Pokhara, Nepal

Abstract: Knowledge deficits and false beliefs were found in both groups, along with a significant use of home remedies and a perception of discrimination against people with hearing impairment. These findings are relevant for healthcare providers and may aid the development of policy, interventions and public education initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Moreover, due to low awareness, parents are unlikely to detect hearing loss until children attain school age. Usually, affected children present with delays in speech and language development and poor performance in school [ 2 , 7 , 40 , 41 ]. Moreover, we found that only 1 in 4 parents correctly suspected that their child had an ear infection while the majority of the parents suspected an ear infection when it did not exist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, due to low awareness, parents are unlikely to detect hearing loss until children attain school age. Usually, affected children present with delays in speech and language development and poor performance in school [ 2 , 7 , 40 , 41 ]. Moreover, we found that only 1 in 4 parents correctly suspected that their child had an ear infection while the majority of the parents suspected an ear infection when it did not exist.…”
Section: Discussionmentioning
confidence: 99%
“…This practice should be shunned. Factors associated with risky health-seeking behaviour include lack of awareness, poverty, beliefs, and unfavorable health systems [ 19 , 29 , 32 , 40 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Optimal health seeking behaviour often depends on accessibility of health facilities coupled with knowledge and understanding of the benefit of modern medical treatment as opposed to local customs and beliefs [ 21 – 23 ]. Regarding use of traditional medicine, the WHO states that “rampant poverty is the prime cause for use, misuse and abuse of traditional medicine” [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that lack of awareness leads the patients to delay care seeking. This is true not only in Rwanda [ 18 ] but also in other regions [ 26 , 27 ]. Chandrashekharayya SH.…”
Section: Discussionmentioning
confidence: 99%